Radioactivity in the Southern East Baghdad Oilfield from the Reservoir to the Surface Environment - Ibrahim , Maryam A.; Ali , Kamal K. (Iraqi Journal of Science, 2024)
Naturally occurring radioactivity was evaluated in the reservoir rock, surface soil samples, and oil production waste at the East Baghdad South (EBS) Oil Field. The radioactivity of uranium-238 (and radium-226), thorium-232, and potassium-40 were calculated in core samples from four geological formations: Al-Zubair, Al-Khasib, Tanuma, and Hartha Formations, which represent the oil reservoirs in the study area in addition to the natural GR and SGR logs for the oil well in EBS were calculated. The radioactivity of the above-mentioned nuclides was also measured for surface soil samples and waste samples from the site of the oil production industry at the EBS oilfield. The measurements included all the stages of oil production from the collection of crude oil from the wells stage to the storage of the manufactured oil. It also included measurements of radioactivity in samples for some sites outside the industry and near the oil wells in the region. Total radioactivity was measured in count/second and the exposure dose rates were also measured at all the above sites. Relatively high concentrations of uranium-238 and radium-226 were found in rock core samples of some geological units within the oil reservoir formations which will certainly move with the oil to the surface and collect with waste (such as sludge) when oil is produced. Although, some sites have higher Ra-226, Th-232, and K-40, in the sludge samples and oily soil, such as in the 1st separator stage, water separation (Desalter) stage, and near the waste pit, these locations are acceptable if they are compared with other oilfields worldwide. The gamma absorbed doses calculated inside the EBS oil industry were higher than the global average of (59) nGy/h where Ra-226 is the main contributor in these doses, on the other hand, external hazard index (Hex) values less than unity so they are acceptable according to UNSCEAR. Radiation dose values in some places in the study area exceed the values recommended by ICRP, UNSCEAR, and IAEA (1 mSv/y) for the public but less than the values recommended for workers (20 mSv/y). generally, the site of EBS- oilfield does not show radioactive contamination or significant radioactive hazards, as it is a new facility, and safety instructions are still strictly applied, and the removal of waste immediately before its spread by the activity of the workers in the facility.